2015
DOI: 10.1093/jb/mvv102
|View full text |Cite
|
Sign up to set email alerts
|

Determination of cleavage site of Reelin between its sixth and seventh repeat and contribution of meprin metalloproteases to the cleavage

Abstract: Reelin is a secreted glycoprotein whose function is regulated by proteolysis. One of the specific cleavage sites of Reelin, called C-t, is located approximately between the sixth and seventh Reelin repeat but its exact site was unknown. We here show that a metalloprotease present in the culture supernatant of cerebellar granular neurons (CGN) cleaves Reelin between Ala2688 and Asp2689. A Reelin mutant in which Asp2689 is replaced by Lys (Reelin-DK) is resistant to C-t cleavage by culture supernatant of CGN. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…WC cleavage occurs between Arg3455 and Ser3456, which is only six amino acid residues from the C-terminus and does not affect the apparent mobility in SDS-PAGE 14 . N-t cleavage dramatically decreases Dab1 phosphorylation by Reelin 30,31 , while C-t or WC cleavage modulate it 14,32 .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…WC cleavage occurs between Arg3455 and Ser3456, which is only six amino acid residues from the C-terminus and does not affect the apparent mobility in SDS-PAGE 14 . N-t cleavage dramatically decreases Dab1 phosphorylation by Reelin 30,31 , while C-t or WC cleavage modulate it 14,32 .…”
Section: Introductionmentioning
confidence: 95%
“…C-t cleavage occurs between Ala2688 and Asp2689, resulting in two fragments with molecular masses of 330 kDa (NR6) and 100 kDa ( Fig. 1A) 32 . WC cleavage occurs between Arg3455 and Ser3456, which is only six amino acid residues from the C-terminus and does not affect the apparent mobility in SDS-PAGE 14 .…”
Section: Introductionmentioning
confidence: 99%
“…C-terminus and does not affect the apparent mobility in SDS-PAGE 14 . N-t cleavage dramatically decreases Dab1 phosphorylation by Reelin 30,31 , while C-t or WC cleavage modulate it 14,32 .…”
mentioning
confidence: 95%
“…C-t cleavage occurs between Ala2688 and Asp2689, resulting in two fragments with molecular masses of 330 kDa (NR6) and 100 kDa (Fig. 1A) 32 . WC cleavage occurs between Arg3455 and Ser3456, which is only six amino acid residues from the open Scientific RepoRtS | (2020) 10:4471 | https://doi.org/10.1038/s41598-020-61380-w www.nature.com/scientificreports www.nature.com/scientificreports/ Figure 1.…”
mentioning
confidence: 99%
“…Meprin α processes proMMP-9 and enhances its activation kinetics (Geurts et al, 2012). Additionally, meprin α is able to cleave proteins that are related to synaptic plasticity, such as Reelin (Sato et al, 2016) and vasoactive intestinal peptide (Sterchi et al, 2008). In addition, studies in non-mammalian species have demonstrated a role for Tll proteases in learning.…”
Section: Introductionmentioning
confidence: 99%